O fenômeno das emoções no jovem Sartre - Bueno, Caroline de Paula (2022)
The research currently under way has as its central focus the phenomenological theory of emotions as it takes place in Sartre's youth work, The Emotions: Outline of a Theory (1939). In this direction, the dissertation starts from the general objective that consists, initially, in determining the intentional structure of emotion in its phenomenal figuration. To this end, the work aims to reconstruct the Sartrean critique of the classical theories of emotions mainly established by the physiological and psychoanalytic schools. Furthermore, at the last moment, we will seek to confront the Sartrean theoretical position itself, with Goldstein's organismic conception. Therefore, the research is justified, above all, by the relevance of the theme that is still little theoretically treated from the perspective of psychological studies via a more strictly phenomenological orientation. We can then, summarily, summarize the thesis advocated by Sartre that the phenomenon of emotion constitutes a transcendental essence and, to that extent, emotion itself reveals itself, above all, as a form of existence of consciousness insofar as it must transcend herself. Now, this singular mode of existence can only be understood against a radical background: the experience of the lived world. It is about our surroundings, the wider circuit of integral existence. Through this experience, the individual approaches the world in its entirety, understanding that he himself is a transforming agent, so that he can, in fact, act. It is from this basic understanding that the dissertation culminates in rehearsing a fruitful debate with other significant references that, in one way or another, converge or diverge from the Sartrean position, among them, in particular, the clinical writings of the German neuropsychiatrist Kurt Goldstein, such as, in particular, On Emotions: Considerations from Organismic Point of View; this article has as its background The Structure of the Organism (1934). Goldstein understands the relationships between the organism and the environment as dialectically structured. Thus, even though he has some reservations about the Sartrean conception, we understand that this biological-clinical reading does not fundamentally disagree with a good part of the Sartrean phenomenological theses that aim precisely to situate the factual and finite condition of man as a being-in-the-world. This, by the way, also evidences how much emotion is really a way of apprehending the world, that is, a capital phenomenon of every being in a situation.